2007
DOI: 10.1200/jco.2006.08.1331
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine and Soluble Receptor Signature Predicts Outcome of Patients With Classical Hodgkin's Lymphoma: A Study From the Groupe d'Etude des Lymphomes de l'Adulte

Abstract: PurposeApproximately 15% of patients with localized and 30% with disseminated classical Hodgkin's lymphoma fail to respond or relapse after first-line treatment. Usual prognosis scoring systems are actually unable to identify this small subset of patients with good confidence, pointing out the need for additional prognostic biomarkers.Patients and MethodsWe prospectively analyzed the prognosis value of plasma levels of tumor necrosis factor (TNF), its soluble receptors TNF-R1 and TNF-R2, IL-10, IL1-RA, IL-6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 32 publications
4
65
1
4
Order By: Relevance
“…Our findings are similar to cytokine signatures that are associated with poor survival after sepsis (14,15) and cancer (16). We also found that elevated TNFR-I on day 8 was strongly associated with mortality, and lower concentrations were associated with renal recovery.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are similar to cytokine signatures that are associated with poor survival after sepsis (14,15) and cancer (16). We also found that elevated TNFR-I on day 8 was strongly associated with mortality, and lower concentrations were associated with renal recovery.…”
Section: Discussionsupporting
confidence: 86%
“…These mediators can be used as potential prognostic factors during treatment [61][62][63]. Because the HL microenvironment consists of 20%-50% of reactive, polyclonal B cells, elevated serum-free light chain levels can be detected in approximately 30% of the patients and can be predictive of treatment outcome [64].…”
Section: Microenvironmentmentioning
confidence: 99%
“…21 In a recent study, Casasnovas et al also demonstrated that the plasma cytokine signature could be used to predict diseaserelated outcome in cHL. 22 For the proteins identified in this study, additional large-scale studies on HL patient plasma or serum need to be performed to elucidate the possible relation of the 7 potential biomarkers to disease activity.The main goal of this study was to identify new players that might contribute to the pathogenesis of HL. For the chemokines TARC, RANTES, and IP-10, previous studies already demonstrated their putative role and confirmed expression in HRS cells of patient tissues.…”
mentioning
confidence: 99%